Evaluation of the risk of misidentification of women in a public maternity hospital - Terezinha Hideco Tase; Ellen Regina Sevilla Quadrado; Daisy Maria Rizatto Tronchin
ABSTRACT Objective: To determine the frequency of similar names and hospital records of women in a public teaching maternity hospital and the risk of misidentification resulting from the similarity in spelling and pronunciation of the names and in records. Method: Quantitative, documental and case study of 5,975 admissions that occurred between 2011 and 2014. The data name, admission and discharge date, date of birth, hospital record and bed number were collected from an electronic information system. Analysis encompassed descriptive statistics and design of an algorithm for comparison of text and sound. Results: Examination of the names revealed that 86% of the misidentification cases resulted from identical surnames and 96.5% from a sound similarity in the first names. There were patients with identical first and last names at least one day a week. Conclusion: The risk of misidentification of patients is a reality, which stresses the importance of checking and pronouncing the complete names correctly.